Identification Of Escherichia Coli Bacterial Contamination in Home Industry Baby Porridge In The Malang City Area - Dafin, Anis Akhwan; Putri, Elsa Mahardika; Prasetyawan, Fendy; Muslikh, Faisal Akhmal; Ma’arif, Burhan; Megawati, Dewi Sinta (International Journal of Contemporary Sciences (IJCS), 2023)
Growth and development in toddlers is very important, especially the nutritional needs of toddlers. MP-ASI is additional food to provide sufficient nutrition for babies. MP-ASI is divided into two types, namely traditional and industrial. Traditional MP-ASI is baby porridge that is prepared by yourself and sold on the side of the road. Hygiene and sanitation in roadside food can have a negative impact on consumers, especially bacterial contamination of food, one of which is Coliform bacteria, Escherichia Coli, etc. The method for calculating and estimating the number of E. coli bacteria found in chicken meat in this study used the Most Probable Number (MPN). The results showed that of the 4 samples tested, 3 were contaminated with E. Coli bacteria and 1 was negative for E. Coli bacterial contamination